+0  
 
0
41
1
avatar

The quadratic ax^2 + bx + c can be expressed in the form 2(x - 8)^2 + 4. When the quadratic 3ax^2 + 2bx + c is expressed in the form n(x - h)^2 + k, what is h?

 Aug 3, 2022
 #1
avatar+124596 
+1

2(x- 8)^2  + 4   =

 

2 (x^2 -16x + 64) + 4

 

2x^2 - 32x + 128 + 4

 

2x^2 - 32x  + 132                   a = 2    b  =  -32          c = 132

 

So

 

3ax^2  + 2bx + c   =

 

8x^2 - 64x + 132  =

 

8 ( x^2 - 8x )  + 132             complete the square on  x

 

8 ( x^2 - 8x + 16) + 132 - 8(16)

 

8 ( x - 4)^2  +  4

 

h =  4 

 

 

cool cool cool

 Aug 3, 2022

13 Online Users